2016
DOI: 10.1111/jcmm.12957
|View full text |Cite
|
Sign up to set email alerts
|

Alternol, a natural compound, exerts an anti‐tumour effect on osteosarcoma by modulating of STAT3 and ROS/MAPK signalling pathways

Abstract: Osteosarcoma (OS) is the most frequent primary malignant bone tumour. Alternol, a novel compound purified from microbial fermentation products exerts anti‐tumour effects across several cancer types. The effect of alternol on human OS remains to be elucidated. We first evaluated the anti‐tumour effect of alternol in several human OS cell lines in vitro and investigated its underlying mechanism. Alternol inhibited OS cell proliferation, migration and induced caspase‐dependent apoptosis, G2/M cell cycle arrest in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 39 publications
6
31
0
Order By: Relevance
“…Natural bioactive compounds derived from traditional Chinese medicinal herbs have been widely investigated because of their antiproliferative, antiangiogenic, and antitumor effects on various diseases, as well as their safety, efficacy and immediate availability. The effects of natural compounds on the inhibition of osteosarcoma have previously been reported by our research team . For instance, we found that pectolinarigenin significantly suppressed osteosarcoma cell proliferation, induced apoptosis and inhibited migration and invasion in osteosarcoma cells .…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Natural bioactive compounds derived from traditional Chinese medicinal herbs have been widely investigated because of their antiproliferative, antiangiogenic, and antitumor effects on various diseases, as well as their safety, efficacy and immediate availability. The effects of natural compounds on the inhibition of osteosarcoma have previously been reported by our research team . For instance, we found that pectolinarigenin significantly suppressed osteosarcoma cell proliferation, induced apoptosis and inhibited migration and invasion in osteosarcoma cells .…”
Section: Discussionsupporting
confidence: 72%
“…Our team previously reported that STAT3 is a critical regulator of osteosarcoma development and progression . The effect of RA on the JNK and STAT3 signaling pathways was assessed to investigate the molecular mechanism of the antitumor activity of RA using pharmacological inhibitors and shRNA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the media were carefully removed by aspiration. Colonies were stained by crystal violet, photographed, and scored [24]. …”
Section: Methodsmentioning
confidence: 99%